Menggali Potensi Siswa: Pembelajaran Tematik di Kelas 3 Madrasah Ibtidaiyah NW 2 Talun Lombok Timur - Huda, Nurul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Education plays a crucial role in shaping a generation that is competent and of high quality. Recognizing this significance, this research endeavors to explore students' potential through the implementation of thematic learning in the 3rd grade of Madrasah Ibtidaiyah NW 2 Talun East Lombok. The primary objective of this research is to investigate the impact of thematic learning on students' understanding, critical thinking skills, and learning motivation, utilizing a qualitative case study research method. Data collection involves classroom observation, interviews with teachers and students, and document analysis. The research findings indicate that the implementation of thematic learning in the context of the 3rd grade of Madrasah Ibtidaiyah NW 2 Talun East Lombok has a positive impact on students' understanding of concepts, critical thinking skills, and learning motivation. Additionally, the case study approach provides in-depth insights into how qualitative thematic learning influences teacher-student interactions and the learning process within the classroom. These findings offer a profound understanding of the effectiveness of thematic learning in enhancing students' potential at the madrasah ibtidaiyah level, and the practical implications of this research can serve as a guide for teachers and decision-makers in developing more contextualized teaching methods. Furthermore, this case study provides a foundation for further research in the context of thematic education in madrasah ibtidaiyah.